Konstruksi Hukum Pembuktian Penuntut Umum Terhadap Surat Dakwaan Yang Disusun Secara Alternatif Dalam Putusan Pengadilan Negeri Sukoharjo - Dinar Mahardiyanti Dewi (Sebelas Maret University, 2013)
This study aims to determine the prosecutor's rationale in drafting legal construction with alternative indictment in the case of under age molestation and the effect of prosecutor evidence against the indictment which made alternatives in proving the defendant's offense.This is prescriptive normative research, discovered the law in abstracto and in concreto on the prosecutor's rationale in drafting legal construction and the effect of prosecutor evidence in proving the defendant's offense. The data used is secondary data. With the sources primary legal materials, legal materials, secondary and tertiary legal materials. This research reveals that, the prosecutor's rationale in drafting legal construction with alternative indictment are the prosecutors uncertainty about the qualifications or the appropriate article to be applied on offense which done by defendant and to minimize the chances of escape of the defendant from the charges. Second, effect of prosecutor evidence against the indictment which made alternatives in proving the defendant's offense are facilitate judges in determining the the defendant guilt and Proven first indictment in indictment. Keywords: Alternative indictment, prosecution, under Age molestation